LANGUAGE MAINTENANCE OF THE JAVANESE INTERMARRIAGES IN RANTAU UTARA - Matrejo Matrejo; Busmin Gurning; Siti Aisyah Ginting (LINGUISTIK TERAPAN, 2018)
This study deals with the Language Maintenance of Javanese Intermarriages in Rantau Utara. It employed qualitative research design with a case study. This study aims to describe: (1) the factors of language maintenance and (2) the the way of Javanese Intermarriages maintained the Javanese language (3) the reasons of Javanese Intermarriages maintained the language. The subjects were 20 Javanese Intermarriages.They were chosen because many of Javanese people who married with other ethnic. The instruments used of this study were observation, questionnaire and interview. The data were analyzed by using Miles,Hubberman and Saldana’s data analysis. The result of the study were found that there were six factors of Javanese language of maintaining the language namely seeing each other frequently (100%), neighborhood domain (97%), ethno linguistic vitality (100%), family domain (99%), religion domain (55%) and practice the traditional ceremony (35%). Then the way of maintaining the javanese language were found namely acquisition of the language (40%), create a socially integrated population of native speakers (60%), localities of habitually using the language (80%) and the last was speak language in area oral competence (35%).The reasons of Javanese Intermarriages maintained the language namely show identity (90%), Pride (100%) and keep the language (100%). Keywords: language maintenance, intermarriages, ethnic